Las obligaciones y contratos mercantiles, en el Derecho peruano: ¿“Pollice verso”? - Garcia Pita, José Luis (Revista de Derecho, 2019)
Peruvian and Spanish Private Law, as in many Civil Law countries, is divided into two great branches known as “Derecho civil” and “Derecho mercantil o comercial”, each one included in a separate Code -Código civil/Código de comercio-, but in both countries exists an important trend prone to unification of Private Contract Law, by way of abrogation of special commercial rules. ¿How far has this trend gone in one country and in the other one? And If it is gone relatively far, ¿is this a good trend or is it a bad one? In this paper, the Author makes a statement prone to survival of commercial special rules, both as an actual fact, and as a better way to resolve problems arising from commercial and consumer transactions.